The protective role of resilience and social support against burnout during the COVID-19 pandemic - Shahwan, Shazana; Tay, Eng Hong; Shafie, Saleha; Tan, Yoke Boon; Gunasekaran, Savita; Tan, Rachel Hsiao Shen; Satghare, Pratika; Zhang, Yunjue; Wang, Peizhi; Tan, Sing Chik; Subramaniam, Mythily (Frontiers in Public Health, 2024)
Background The COVID-19 pandemic brought on a range of stressors in homes and workplaces. With no sign of ending after one year, burnout was a concern. Resilience has been known to shield against the effects of stress. While often thought of as an individual trait, previous studies have shown social support to improve resilience. The study aimed to examine the extent of burnout in the Singapore population and whether social support and resilience cushioned the impact of COVID-19 related stressors a year into the pandemic. Methods Participants were 858 Singapore residents who participated in a larger study between October 2021 and September 2022. The Copenhagen Burnout Inventory provided Work-and Personal-related burnout scores. Multivariable linear regression was used to identify demographic variables associated with burnout. Path analysis revealed the associations between COVID-19 stressors, social support, resilience and burnout. Results 22 and 19% of the sample reported work and personal burnout respectively, with younger adults being more burnt out than older adults. Higher stress was associated with higher burnout and higher social support was associated with lower burnout. Path analysis revealed that the relationship between social support and burnout was partially accounted for by increased resilience. Conclusion Managing altered work arrangements, career expectations, and increased responsibilities at home may contribute to greater levels of burnout in the younger adults. Increased employer support and targeted interventions could mitigate the impact of these stressors. The study also highlighted the importance of maintaining social connections even while physically distancing.